The Role of Young Entrepreneurs in Labor Absorptions and its Implications to Family Economic Resilience - Azhar Ulwan (Research Horizon, 2021)
The purpose of this study is to determine the role of young online convection entrepreneurs in labor absorption and the obstacles faced by young online convection entrepreneurs as well as to analyze the implications of young online convection entrepreneurs in Bantul Regency on their family economic resilience. This research used a qualitative approach. Primary data is obtained from observations and in-depth interviews with 5 young entrepreneurs from 5 different online convection, namely Arto Convection, Apparelsae Convection, Convection San Project, ID Convection, and Indeepco Clothing. The data analysis technique used is interactive model data analysis. This study used data validity checking techniques, namely triangulation, and detailed description techniques. The results of the research showed that young entrepreneurs have a role in labor absorption and provide income to the owner convection. Some of the obstacles often encountered by young entrepreneurs of convection online are a constraint on the production, financial management, management of marketing, customer service online base, less qualified human resources constraints, and constraints background education entrepreneurs who are not majoring in business. Young online convection entrepreneurs have made several efforts to overcome these obstacles. Based on the analysis with the income contribution approach and the basic need approach, the impact of online convection makes the economic resilience of young entrepreneur families strong and resilient.